2022
DOI: 10.1021/acscatal.1c04388
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Sampling of Dihydrofolate Reductase Shows Kinetic Pauses and an Endosteric Effect Linked to Catalysis

Abstract: The ability to sample multiple reactions on the same single enzyme is important to link rare intermediates with catalysis and to unravel the role of conformational changes. Despite decades of efforts, however, the single-molecule characterization of nonfluorogenic enzymes during multiple catalytic turnovers has been elusive. Here, we show that nanopore currents allow sampling the dynamic exchange between five structural intermediates during E. coli dihydrofolate reductase (DHFR) catalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Ligand-induced conformational changes for a range of proteins [78][79][80] have been reported using biological nanopores. These include the tiny conformational changes of dihydrofolate reductase (DHFR) during ligand binding 80 and catalysis 81 , which could not be observed previously by single-molecule fluorescence resonance energy transfer experiments. The results of these studies revealed that DHFR exists in multiple fixed conformations-conformers-whose exchange during catalysis is probably used to tune enzyme efficiency 80,81 .…”
Section: Characterization Of Single Proteins With Nanoporesmentioning
confidence: 85%
See 2 more Smart Citations
“…Ligand-induced conformational changes for a range of proteins [78][79][80] have been reported using biological nanopores. These include the tiny conformational changes of dihydrofolate reductase (DHFR) during ligand binding 80 and catalysis 81 , which could not be observed previously by single-molecule fluorescence resonance energy transfer experiments. The results of these studies revealed that DHFR exists in multiple fixed conformations-conformers-whose exchange during catalysis is probably used to tune enzyme efficiency 80,81 .…”
Section: Characterization Of Single Proteins With Nanoporesmentioning
confidence: 85%
“…d, Catalytic activity of DHFR (coloured according to vacuum electrostatics using PyMOL) inside a ClyA nanopore (grey, top), as shown by representative traces (bottom). Product formation is indicated by pink asterisks81 , which involve the complexes of the enzyme DHFR (E) with NADPH (E:NH), tetrahydrofolate (E:THF) and then dihydrofolate (E:NH:DHF). e, Dynamic conformation of a single peptide confined in a SiN x solid-state nanopore (top left).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by sampling multiple reactions of a single enzyme using ClyA mutant pores (Figure 1B), nanopore currents reveal the conformational dynamics between five intermediate structures during catalysis, and the enzyme reaction can be observed by nanopore sensing at the singlemolecule level. [23] In 2022, Li et al used ClyA-AS mutant nanopores to investigate the morphological changes in the Abelson (Abl) [19] Copyright 2015, WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. (B) Trapping of DHFR with ClyA-AS nanopore, providing distinctive current blockades by transition state responding to DHFR catalytic cycle.…”
Section: Ki-baekmentioning
confidence: 99%
“…Reproduced with permission. [23] Copyright 2022 The Authors. Published by American Chemical Society.…”
Section: Ki-baekmentioning
confidence: 99%